Serum ferritin and ECOG performance status predict the response and improve the prognostic value of IPSS or IPSS-R in patients with high-risk myelodysplastic syndromes and oligoblastic acute myeloid leukemia treated with 5-azacytidine: a retrospective analysis of the Hellenic national registry of myelodysplastic and hypoplastic syndromes. (December 2020) - Papageorgiou, Sotirios G.; Kotsianidis, Ioannis; Bouchla, Anthi; Symeonidis, Argyris; Galanopoulos, Athanasios; Viniou, Nora-Athina; Hatzimichael, Eleftheria; Vassilakopoulos, Theodoros P.; Gogos, Dimitrios; Megalakaki, Aikaterini; Zikos, Panagiotis; Diamantopoulos, Panagiotis; et al.
Background: 5-azacytidine (5-AZA) improves survival of patients with higher-risk myelodysplastic syndromes (MDSs) and oligoblastic acute myeloid leukemia (AML); however, predictive factors for response and outcome have not been consistently studied. Methods: This study of the Hellenic MDS Study Group included 687 consecutive patients with higher-risk MDS and oligoblastic AML treated with 5-AZA. Results: The International Prognostic Scoring System (IPSS) revised version (IPSS-R), Eastern Cooperative Oncology Group Performance Status (ECOG PS) (0 or 1 versus ⩾2) and baseline serum ferritin (SF) levels > 520 ng/ml were shown to independently predict response to 5-AZA. In the survival analysis, the IPSS and IPSS-R risk classification systems along with the ECOG PS and SF levels > 520 ng/ml proved to be independent prognosticators for overall survival (OS), as well as for leukemia-free survival (LFS). Next, we built new multivariate models for OS and LFS, incorporating only ECOG PS and SF levels besides IPSS or IPSS-R risk classification systems. Thereby, the new modified IPSS and IPSS-R risk classification systems (H-PSS, H-PSS-R) could each discriminate a low, an intermediate and a high-risk patient group regarding OS and LFS. The H-PSS and H-PSS-R proved to be better predictors of OS than their previous counterparts as well as the French prognostic score, while the most powerful OS predictor was the new, H-PSS-R system. Conclusions: ECOG PS and SF levels > 520 ng/ml independently predict response to 5-AZA, OS and LFS. Their incorporation in the IPSS and IPSS-R scores enhances these scores' predictive power in 5-AZA-treated higher-risk MDS and oligoblastic AML patients.